Synthesis and characterization of poly{2-[3-(1H-pyrrol-2-yl)phenyl]-1H-pyrrole} and its copolymer with EDOT - Turac, Ersen; Ak, Metin; Sahmetlioglu, Ertugrul; Sener, M. Kasim; Kaya, Mehmet Arif (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2011)
A pyrrole-functionalized monomer 2-[3-(1H-pyrrol-2-yl)phenyl]-1H-pyrrole (PyPhPy) was synthesized. The structure of monomer was investigated by Nuclear Magnetic Resonance (H-1 NMR) and Fourier Transform Infrared (FTIR) spectroscopy. The chemical polymerization of PyPhPy (CPyPhPy) was realized using FeCl3 as the oxidant. The electrochemical oxidative polymerization of polymer P(PyPhPy) and its copolymer with 3,4-ethylenedioxythiophene poly(2-[3-(1H-pyrrol-2-yl)phenyl]-1H-pyrrole-co-3,4-ethylenedioxythiophene) [P(PyPhPy-co-EDOT)] were achieved via potentiodynamic method by using NaClO4/LiClO4 as the supporting electrolyte in CH3CN. Characterizations of the resulting polymers were performed by cyclic voltammetry (CV), FTIR, scanning electron microscopy (SEM), UV-Visible spectrophotometry (UV-Vis) and thermogravimetry analyses (TGA). Electrical conductivity of CPyPhPy, P(PyPhPy), and P(PyPhPyco-EDOT) were measured by four-probe technique.
Keywords: SOLUBLE CONDUCTING POLYMER; ELECTROCHROMIC PROPERTIES; ELECTROCHEMICAL SYNTHESIS; POLYTHIOPHENE; POLYPYRROLE; THIOPHENE; Chemistry